A best–worst scaling in Colombian patients to rank the characteristics of HIV/AIDS treatment. (4th May 2018) - Hendriks, A.; Wijnen, B.; van Engelen, R.; Conde, R.; Evers, S.M.; Gonzalez, J.; Govers, M.; Mühlbacher, A.; Hiligsmann, M.
Abstract: Aim: To elicit patients' preferences for HIV/AIDS treatment characteristics in Colombia. Materials and methods: A best–worst scaling case was used to provide a ranking of 26 HIV/AIDS treatment characteristics that were similar to a previous study conducted in Germany. In each choice task, participants were asked to choose the most important and the least important treatment characteristics from a set of five from the master list. Using the Hierarchical Bayes method, relative importance scores were calculated. Sub-group analyses were conducted according to sex, education, source of infection, symptoms, and age. Results: A total of 195 patients fully completed the questionnaire. The three most important characteristics were "drug has very high efficacy" (relative importance score [RIS] = 10.1), "maximum prolongation of life expectancy" (RIS = 9.7), and "long duration of efficacy" (RIS = 7.4). Sub-group analysis showed only three significant (but minor) differences between older and younger people. Conclusion: This study suggests that treatment characteristics regarding efficacy and prolongation of life are particularly important for patients in Colombia. Further investigation on how patients make trade-offs between these important characteristics and incorporating this information in clinical and policy decision-making would be needed to improve adherence with HIV/AIDS medication.